A highly purified C-phycocyanin from thermophilic cyanobacterium Thermosynechococcus elongatus and its cytotoxic activity assessment using an in vitro cell-based approach. Issue 1 (1st January 2020) - El-Mohsnawy, Eithar; Abu-Khudir, Rasha
ABSTRACT: C-phycocyanin (C-PC) is a protein–pigment widely used in nutrition and pharmaceutical applications. High purity of C-PC is a limiting factor required for its medical use; hence purity improvement with successful plausible pharmaceutical application is the state of the art of the present work. Highly purified C-PC (A620 /A280  = 6.6) was obtained from Thermosynechococcus elongatus . Combined enzymatic cell wall degradation, cellular exposure to high pressure, sonication, and one-time homogenization was found to be an effective purification protocol. Purified complex was confirmed by SDS-PAGE and UV-absorption spectral analysis. Cytotoxic effect of the obtained C-PC was assessed in vitro using a panel of cancer cells. Results showed that MCF-7 cells were most sensitive to C-PC (IC50  = 158.9 µM) compared to Caco-2 (IC50  = 258.3 µM) and HepG2 (IC50  = 277.5 µM) cells. Our findings shed the light on the potential medical use of C-PC isolated from T. elongatus in controlling cancer cells.